Developing a fully function of e-transaction framework towards digital local government services - Wallang, Muslimin; Shariffuddin, Mohd Dino Khairri (2019)
During the Eighth Malaysia Plan period, a total of RM7.885 billion was allocated for ICT-related programs and projects, and the amount allocated under the Ninth Malaysia Plan for ICT development was RM12.889 billion. Malaysia has successful cases of implementing e-government services. However, a recent study about e-service adoption in Malaysia indicated that it was growing slowly with a low rate of adoption. Despite the enormous research efforts that have been put forth, e-transaction services offered by the government agencies often remain underutilized. Studies found that citizens were more likely to use e-information services than etransaction services, even with both services were offered online in the same webpage. As such, it is reasonable for this study to understand the reasons why e-transaction service failed to attract the public to use it. Besides to determine the key factors that related to the e-transaction use, the objectives of the study also to classify the barriers that lead to the less usage of e-transaction; and based on the usage pattern on e-transaction service, the development of comprehensive framework will be proposed.